MagR Alone Is Insufficient to Confer Cellular Calcium Responses to Magnetic Stimulation - Pang, Keliang; You, He; Chen, Yanbo; Chu, Pengcheng; Hu, Meiqin; Shen, Jianying; Guo, Wei; Xie, Can; Lu, Bai (Frontiers in Neural Circuits, 2017)
Magnetic manipulation of cell activity offers advantages over optical manipulation but an ideal tool remains elusive. The MagR protein was found through its interaction with cryptochrome (Cry) and the protein in solution appeared to respond to magnetic stimulation (MS). After we initiated an investigation on the specific role of MagR in cellular response to MS, a subsequent study claimed that MagR expression alone could achieve cellular activation by MS. Here we report that despite systematically testing different ways of measuring intracellular calcium and different magnetic stimulation protocols, it was not possible to detect any cellular or neuronal responses to magnetic stimulation in MagR-expressing HEK cells or primary neurons from the dorsal root ganglion and the hippocampus. By contrast, in neurons co-expressing MagR and channelrhodopin, optical but not magnetic stimulation increased calcium influx in hippocampal neurons. Our results indicate that MagR alone is not sufficient to confer cellular magnetic responses.